Creativity Profile Of Medical Laboratory Technology Students In Medical Instrumentation Learning - Iswari pauzi; Aliefmam Hakim; Aris Doyan; Gito Hadiprayitno; Joni Rokhmat; A.A Sukarso (Jurnal Analis Medika Biosains (JAMBS), 2023)
The aim of the study was to describe the creativity profile of students of the Applied Undergraduate Study Program of Medical Laboratory Technology, Health Polytechnic, Ministry of Health, Mataram. The research method used is descriptive research. Data was collected through a questionnaire made using the Google form and then distributed to research respondents totaling 52 students. The data analysis technique used is descriptive analysis using the percentage of each indicator. The results showed that students' critical thinking skills were low on indicators of providing further explanations and drawing conclusions, and creative thinking skills were low for students to think fluently and originally.